1993
DOI: 10.1159/000156738
|View full text |Cite
|
Sign up to set email alerts
|

Annual Birth Patterns of Savanna Baboons (Papio cynocephalus anubis) over a Ten-Year Period at Gilgil, Kenya

Abstract: Most cercopithecines reproduce on a seasonal basis, but the proximate mechanisms influencing birth periodicity are often unclear. We analyze 10 years of data from the Gilgil Baboon Project (Kenya) in order to examine the relationship between annual birth patterns and rainfall. Savanna baboons at Gilgil copulated in all months of the year, and births did not occur on a seasonal basis. Annual rainfall patterns showed no association with annual birth patterns, but the chances of conception were significantly grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Baboons typically show an even distribution of reproduction throughout the year, with no strong seasonal birth peaks (Altmann et al, 1988;Bercovitch and Harding, 1993). We found a slight seasonal trend in births but only for females in Park 5, with a peak in February and a trough in July-August.…”
Section: Discussionsupporting
confidence: 44%
“…Baboons typically show an even distribution of reproduction throughout the year, with no strong seasonal birth peaks (Altmann et al, 1988;Bercovitch and Harding, 1993). We found a slight seasonal trend in births but only for females in Park 5, with a peak in February and a trough in July-August.…”
Section: Discussionsupporting
confidence: 44%
“…Late-life survival as seen today seldom (if ever) occurred among any human population before the advent of settled agriculture. Such extended late-life survival also does not exist among extant apes; even in captivity their maximum life span is well under 60 years (Bercovitch and Harding, 1993;Crews, 2003;Crews and Gerber, 2003). Rather, long life evolved because the development of culture reduced child and adult mortality hazards, provided a safe, secure and constant microenvironment conducive to growth and development of less physically mature offspring compared to other hominids, and released energetic supplies previously needed for PI and for the maintenance of one's own adult soma, to be invested in RC through greater SI (see Crews, 2003 for a more thorough review).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in populations living in nonseasonal environments or in areas with unpredictable mast years (some baboons and macaques), females conceive during peak food availability. [65][66][67] Here, ecological conditions act directly on the timing of conceptions. Birth seasons or peaks are the secondary consequence of conception peaks.…”
Section: Box 2 (Continued)mentioning
confidence: 99%
“…Birth seasons or peaks are the secondary consequence of conception peaks. 67 With regard to Hanuman langurs, Bishop 17 suggested that the timing of births was optimal because plant flowering and flushing in spring may indicate the availability of highquality food. In contrast, Kankane 59 and Sommer and Rajpurohit 11 proposed that the high abundance of food during the monsoon might improve the nutritional status of females, which in turn would enable the females to cycle and conceive.…”
Section: Box 2 (Continued)mentioning
confidence: 99%